Evaluation of a poaching catch for kaluga Huso dauricus and amur sturgeon Acipenser schrenckii (Acipenseridae) - V. N. Koshelev; D. S. Didenko; L. A. Zykov; A. P. Shmigirilov (Известия ТИНРО, 2022)
Estimations of a poaching catch in the Amur estuary for kaluga and amur sturgeon are presented. Total illegal catch of these species in 2011 and 2016 is amounted as 8,300 and 15,060 ind. or 409.1 and 745.0 t, respectively. The volume of poaching on kaluga and amur sturgeon exceeded in 1–2 orders (in 26–268 times) the legal catch for research purposes and artificial reproduction. The poaching in the Amur is relatively stable through decades.